Political affect : connecting the social and the somatic - Protevi, John, 1955- (Posthumanities, 2009)
Political Affect investigates the relationship between the social and the somatic: how our bodies, minds, and social settings are intricately linked. Bringing together concepts from science, philosophy, and politics, he develops a perspective he calls political physiology to indicate that subjectivity is socially conditioned and sometimes bypassed in favor of a connection of the social and the somatic, as with the politically triggered emotions of rage and panic.